1985
DOI: 10.1093/sleep/8.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake State Organization, Neonatal Assessment and Development in Premature Infants During the First Year of Life. II.

Abstract: Summary: Twenty four premature infants were evaluated in their homes at seven ages during the first year of life to determine whether sleep-wake state organization was related to either neonatal assessment or short-term developmental outcome measures. A model assessing environmental and biological influences on the maturational course of selected sleep-wake state parameters was also evaluated. Sleepwake state variables and neonatal assessment items were related to each other, and both predicted developmental q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 14 publications
2
78
1
1
Order By: Relevance
“…The dramatic developmental decrease in active sleep over the preterm period makes possible the increases in quiet sleep and waking states Ingersoll & Thoman, 1999). Several other researchers have also found that the active sleep or its criteria are related to developmental problems in preterm and fullterm infants Whitney & Thoman, 1993) although other researchers have found that other sleeping and waking behaviors-particularly waking, crying, or quiet sleep-were better predictors of developmental outcomes (Anders et al, 1985;DiPietro & Porges, 1991;Gertner et al, 2002). However, only Anders et al and our study examined the developmental patterns of these behaviors, rather than the amounts at specific ages.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The dramatic developmental decrease in active sleep over the preterm period makes possible the increases in quiet sleep and waking states Ingersoll & Thoman, 1999). Several other researchers have also found that the active sleep or its criteria are related to developmental problems in preterm and fullterm infants Whitney & Thoman, 1993) although other researchers have found that other sleeping and waking behaviors-particularly waking, crying, or quiet sleep-were better predictors of developmental outcomes (Anders et al, 1985;DiPietro & Porges, 1991;Gertner et al, 2002). However, only Anders et al and our study examined the developmental patterns of these behaviors, rather than the amounts at specific ages.…”
Section: Discussionmentioning
confidence: 51%
“…Sleep-wake measures during the preterm period-including the amount of crying, sleep cycle length, state organization quality, and amount of night sleep-predict Bayley scores during the first year (Borghese, Minard, & Thoman, 1995;DiPietro & Porges, 1991;Fajardo, Browning, Fisher, & Paton, 1992;Gertner et al, 2002). Developmental changes in the amounts of specific sleep behaviors during the first year are related to outcomes in the second year (Anders, Keener, & Kraemer, 1985;Whitney & Thoman, 1993). Further, the stability of sleep-wake patterns in the neonatal period predicts later development (Thoman, Denenberg, Sieval, Zeidner, & Becker, 1981;Whitney & Thoman, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for using time-lapse video recording in the home has been described previously, as have the methods of recording and scoring the videotapes for sleep and waking states Anders, Keener, & Kraemer, 1985;Anders & Sostek, 1976).…”
Section: Methodsmentioning
confidence: 99%
“…The camera was secured on a tripod that overlooked the crib and a microphone was placed nearby to record infant vocalizations. were scored according to standard methods described previously Anders, Keener & Kraemer, 1985;Anders & Sostek, 1976). All coders completed a blinded training, reliability process.…”
Section: Methodsmentioning
confidence: 99%
“…Disrupting sleep and sleep cycles profoundly affects the creation of permanent neural circuits, interfering with the early process of sensory and brain development (Graven & Browne, 2008), which has sometimes led to developing attention problems in later life and adverse neurodevelopmental outcomes (O'Callaghan et al, 2010). Progressive lengthening of sleep periods was related to better mental development in later life, with long periods of uninterrupted sleep predicting better mental development at 12 months (Anders, Keener, & Kraemer, 1985). Therefore, sleep is an important determinant of infants' developmental outcomes (Arditi-Babchuk et al, 2009;A.…”
Section: Sleep Is Important For Infants' Neurosensory Developmentmentioning
confidence: 99%